Egr2-guided histone H2B monoubiquitination is required for peripheral nervous system myelination - Wüst, Hannah; Wegener, Amelie; Fröb, Franziska; Hartwig, Anna; Wegwitz, Florian; Kari, Vijayalakshmi; Schimmel, Margit; Tamm, Ernst R.; Johnsen, Steven A.; Wegner, Michael; Sock, Elisabeth (Nucleic Acids Research, 2020)
Schwann cells are the nerve ensheathing cells of the peripheral nervous system. Absence, loss and malfunction of Schwann cells or their myelin sheaths lead to peripheral neuropathies such as Charcot-Marie-Tooth disease in humans. During Schwann cell development and myelination chromatin is dramatically modified. However, impact and functional relevance of these modifications are poorly understood. Here, we analyzed histone H2B monoubiquitination as one such chromatin modification by conditionally deleting the Rnf40 subunit of the responsible E3 ligase in mice. Rnf40-deficient Schwann cells were arrested immediately before myelination or generated abnormally thin, unstable myelin, resulting in a peripheral neuropathy characterized by hypomyelination and progressive axonal degeneration. By combining sequencing techniques with functional studies we show that H2B monoubiquitination does not influence global gene expression patterns, but instead ensures selective high expression of myelin and lipid biosynthesis genes and proper repression of immaturity genes. This requires the specific recruitment of the Rnf40-containing E3 ligase by Egr2, the central transcriptional regulator of peripheral myelination, to its target genes. Our study identifies histone ubiquitination as essential for Schwann cell myelination and unravels new disease-relevant links between chromatin modifications and transcription factors in the underlying regulatory network.
CRIS-Team Scopus Importer:2020-10-02

Epigenetic regulation in myelinating glia: the role of histone 2b monoubiquitination in Schwann cells - Wüst, Hannah; Wegener, Amelie; Johnson, S.; Fröb, Franziska; Wegner, Michael; Sock, Elisabeth (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

H2B monoubiquitination is essential for peripheral myelination and guided by Egr2 in Schwann cells - Wüst, Hannah; Wegener, Amelie; Fröb, Franziska; Hartwig, Anna; Wegwitz, F.; Kari, V. L.; Schimmel, M.; Tamm, E. R.; Johnsen, S. A.; Wegner, Michael; Sock, Elisabeth (GLIA, 2021)
CRIS-Team WoS Importer:2021-07-16

Sp2 is the only glutamine-rich Specificity protein with minor impact on development and differentiation in myelinating glia. - Wegener, Amelie; Küspert, Melanie; Sock, Elisabeth; Philipsen, Sjaak; Suske, Guntram; Wegner, Michael (Journal of Neurochemistry, 2017)
Oligodendrocytes and Schwann cells are the myelinating glia of the vertebrate nervous system and by generation of myelin sheaths allow rapid saltatory conduction. Previous in vitro work had pointed to a role of the zinc finger containing specificity proteins Sp1 and Sp3 as major regulators of glial differentiation and myelination. Here, we asked whether such a role is also evident in vivo using mice with specific deletions of Sp1 or Sp3 in myelinating glia. We also studied glia-specific conditional Sp2- and constitutive Sp4-deficient mice to include all related glutamine-rich Sp factors into our analysis. Surprisingly, we did not detect developmental Schwann cell abnormalities in any of the mutant mice. Oligodendrocyte development and differentiation was also not fundamentally affected as oligodendrocytes were present in all mouse mutants and retained their ability to differentiate and initiate myelin gene expression. The most severe defect we observed was a 50% reduction in Mbp- and proteolipid protein 1 (Plp1)-positive differentiating oligodendrocytes in Sp2 mutants at birth. Unexpectedly, glial development appeared undisturbed even in the joint absence of Sp1 and Sp3. We conclude that Sp2 has a minor effect on the differentiation of myelinating glia, and that glutamine-rich Sp proteins are not essential regulators of the process. (Figure presented.).
EVALuna2:33488
Keywords: C2H2 zinc-finger proteins; glia; myelin; oligodendrocyte; Schwann cell